下顎歯肉への転移を契機に発見された肺腺扁平上皮癌の1例 - 町田, 好聡; 山本, 学; 家森, 正志; 野井, 将大; 越沼, 伸也; 村上, 翔子 (日本口腔外科学会雑誌, 2020)
Metastatic tumors from other organs to the oral and maxillofacial region are relatively rare. To the best of our knowledge, only six cases of oral metastatic tumors from lung adenosquamous carcinomas have been reported in Japan to date. Here we report a case of lung adenosquamous carcinoma that was initially detected as a metastatic tumor of the gingiva. An 80-year-old man presented with a tumor on the gingiva in the right mandibular region. The differential diagnoses following an incisional biopsy were poorly-differentiated adenocarcinoma, nonkeratinizing squamous cell carcinoma, and poorly-differentiated mucoepidermoid carcinoma. Positron emission tomography-computed tomography revealed abnormal accumulations in the right mandible, right cervical lymph nodes, right lung and regional lymph nodes, and stomach. Lung biopsy revealed that the primary tumor was lung cancer (adenosquamous carcinoma) that had metastasized to the mandibular gingiva. Four courses of carboplatin plus a nonplatinum-based regimen were provided, but the patient presented with progressive disease. Similar findings were observed after a second treatment with three courses of S-1 chemotherapy. Despite the provision of the best supportive care, the general condition of the patient worsened, and he eventually died.